Correlation between diurnal variation of intraocular pressure, ocular pulse amplitude and corneal structural properties - Villas-Bôas,Flávia Silva (2009)
PURPOSE: The purpose of this study was to evaluate the fluctuation of intraocular pressure measurements obtained by Goldmann applanation tonometry, dynamic contour tonometry, and corneal compensated non-contact tonometry during office hours in glaucoma and healthy participants. This study also aims at correlating the intraocular pressure fluctuations with fluctuations of corneal hysteresis, central corneal thickness, mean central corneal curvature and ocular pulse amplitude. METHODS: A total of 12 controls (24 eyes) and 21 patients (38 eyes) with open-angle glaucoma were recruited. Intraocular pressure measured by Goldmann applanation tonometry, dynamic contour tonometry and corneal compensated non-contact tonometry, ocular pulse amplitude, central corneal curvature and thickness, corneal hysteresis, and resistance factor were obtained at intervals of 2 hours, between 9 AM and 5 PM. RESULTS: Intraocular pressure fluctuated significantly throughout the day in controls and glaucoma individuals with all tonometers (P<0.001). There was no statistically significant variation in mean corneal curvature (P=0.048 in controls; P=0.04 in glaucomatous) or hysteresis over time (P=0.12 in controls; P=0.36 in glaucomatous). The ocular pulse amplitude showed a significant diurnal fluctuation in both groups (P<0.001). There was a significant correlation between the intraocular pressure measured by dynamic contour tonometry and ocular pulse amplitude (P<0.001). CONCLUSION: There was significant intraocular pressure fluctuation over office hours on measurements performed by Goldmann applanation tonometry, dynamic contour tonometry, and corneal compensated non-contact tonometry in normal and glaucoma individuals. Intraocular pressure varied independently of corneal hysteresis, central corneal thickness, and central curvature variation. However, there was significant correlation between ocular pulse amplitude and intraocular pressure measurements performed by dynamic contour tonometry.